Overview of Risk Factors in Children with Autism Spectrum Disorders (ASD) at SLB Negeri 1 Makassar - Sabir, firjatullah feniah; Rauly Ramadhani; Najamuddin Andi Palancoi; Ulfah Rimayanti; Abd.Rahim Yunus (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2025)
Autism Spectrum Disorder (ASD) is a developmental disorder of the nervous system that can occur from birth or infancy. Children with ASD have difficulty developing social relationships with others. This autism condition affects social interaction, communication, and behavior that is seen before the child reaches the age of 3 years. The purpose of this study was to describe the risk factors in children with GSA at SLB Negeri 1 Makassar. This study employs a descriptive cross-sectional approach to investigate risk factors in children with GSA at SLB Negeri 1 Makassar. This research was conducted at the Makassar State SLB 1 Educational Institution from January 04 to January 24, 2023. The total number of samples in this study was 61, which fit the inclusion and exclusion criteria. Data processing and analysis were computerized using SPSS 20.0. The majority of children had genetic factors (59.0%). The age of the father when the mother conceived the child was highest in the 29-30 year age category, and the age of the mother when she conceived the child was highest at 32-34 years. Most mothers' education was found to be at the high school level (60.7%). Almost all mothers had a history of passive smoking (90.2%). No mother had a history of exposure to pesticides, alcohol consumption, consumption of antidepressant drugs, or consumption of anti-epileptic medications. Almost all mothers had no history of preeclampsia (90.2%). Most had a history of preterm (67.0%) and LBW (55.7%). Almost all children had a history of asphyxia (95.1%). Most children had a history of febrile seizures (70.5%). Risk factors that are commonly found in children with GSA in SLB Negeri 1 Makassar are genetic history, father's age is 29-30 years and mother's age is 32-34 years, history of high school education, history of passive smoking, history of prematurity, history of LBW, history of asphyxia and history of febrile seizures.